The Effect of Oxytocin Massage on Uterine Involution in Postpartum Mothers at TPMB R, Purwakarta Regency in 2024 - Tarigan, Anita Sari (CV. Publikasi Indonesia, 2025)
Background: Slow uterine involution during postpartum may increase the risk of bleeding and infection. One effective non-pharmacological method is oxytocin massage to stimulate the release of the hormone oxytocin, which helps with uterine contractions. Objective: To determine the effect of oxytocin massage on the acceleration of uterine involution in postpartum mothers. Methods: Quantitative research with quasi-experiment design using pretest-posttest control group design. A sample of 40 postpartum mothers at TPMB R Purwakarta Regency was divided into an intervention group (oxytocin massage) and a control group (routine care). Uterine involution is measured on the 1st, 3rd, and 7th days postpartum. Data analysis used independent t-test and paired t-test. Results: The average decrease in uterine fundus height in the intervention group was faster than in the control group with significant differences (p < 0.05). Conclusion: Oxytocin massage effectively accelerates uterine involution in postpartum mothers.